ProspekPengembanganUbiKayu di KabupatenTrenggalek - IDA SYAMSU ROIDAH (Jurnal AGRIBIS, 2020)
ABSTRACT The aim of this research is to know the prospect of cassava development in Trenggalek Regency.Where the development of the cassava commodity is still wide open in order to increase farmers' income.The data obtained for writing this study uses secondary data by looking at some of the literature in other articles that support this research.The results showed that the productivity of cassava in Trenggalek Regency could be increased by adopting technology, while the prospect of developing cassava was still very promising with the coordination between the production, processing and marketing sectors.The conclusion in this study is that the industrial sector requires an effective and efficient supply of cassava farmers. Keywords: prospect, development, cassava